Analysis and Comparison of indicators for evaluation of Smart Cities development - Boahemaah, Adwoa (Univerzita Pardubice, 2024)
The thesis analyses indicators used to evaluate development of Smart Cities and compares selected cities in terms of most relevant indicators. It contains a procedure for solving this issue, which consists of the analysis of the secondary data. Selected Smart Cities are compared, the results are discussed, and the recommendations are provided. the results are discussed, and the recommendations are provided
Analýza a porovnání indikátorů pro hodnocení rozvoje Smart Cities
Keywords: Smart Cities; indexy; indikátory; analýza; porovnání; Smart Cities; indexes; indicators; analysis; comparison